Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1365-2133.2008.08817.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility testing and resistance phenotype detection inStaphylococcus aureusstrains isolated from patients with atopic dermatitis, with apparent and recurrent skin colonization

Abstract: Discrepancies in antibiotic sensitivity pattern were observed among S. aureus strains colonizing different sites of AD skin (lesional and nonlesional areas), and also in AD patients with prior antibiotic treatment. Therefore, clinicians should consider repeat microbial susceptibility testing on different body sites of patients with AD when clinically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
(61 reference statements)
2
28
0
3
Order By: Relevance
“…Nonlesional skin also exhibited decreased diversity relative to controls, suggesting an altered cutaneous microbiota beyond clinically affected skin in AD patients. While culture-based studies have shown increased rates of Staphylococcus colonization on nonlesional skin, 29,30 molecular characterization of the nonlesional cutaneous microbiome and how it differs from control skin using both qPCR and 16Ss sequencing had not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlesional skin also exhibited decreased diversity relative to controls, suggesting an altered cutaneous microbiota beyond clinically affected skin in AD patients. While culture-based studies have shown increased rates of Staphylococcus colonization on nonlesional skin, 29,30 molecular characterization of the nonlesional cutaneous microbiome and how it differs from control skin using both qPCR and 16Ss sequencing had not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis (AD), a common form of eczema, affects up to 20% of children in the US, and is widely accepted to have a profound defect in the stratum corneum function and increased transepidermal water loss (Choi and Maibach, 2005; Imokawa, 2001; Jungersted et al ., 2008; Laughter et al ., 2000; Murata et al ., 1996; Pilgram et al ., 2001). AD patients are far more susceptible to skin infections by organisms such as Staphlococcus aureus and Herpes simplex (Kedzierska et al ., 2008; Lebre et al ., 2008; Niebuhr et al ., 2008; Scott et al ., 2007). It has been speculated that AD individuals would be more susceptible to severe radiation skin injury, however the definitive answer has yet to be elucidated.…”
Section: Current Understanding: Perception Of Radiation Skin Injurymentioning
confidence: 99%
“…However, the benefit of antibiotic use in AD is still disputed with a Cochrane review presenting studies showing no significant difference in global outcome for clinically infected eczema when oral antibiotics were compared with placebo or when topical steroid antibiotic combinations were compared with steroid alone [50]. Given the contradictory results available, it would be prudent to be restrictive in prescribing antibiotics, mainly because of an increasing resistance problem worldwide [55, 56, 57, 58]. …”
Section: The Rationale For Antiseptic Use In Atopic Eczemamentioning
confidence: 99%